2020
DOI: 10.3390/infrastructures5040031
|View full text |Cite
|
Sign up to set email alerts
|

The Governance Approach of Smart City Initiatives. Evidence from Trondheim, Bergen, and Bodø

Abstract: A pragmatic and polity-focused solution for governing a smart city in the direction of sustainability is still missing in theory and practice. A debate about whether a smart city is a pragmatic solution for modern challenges or just a technology-led urban utopia is entangled with the vexed issue of governance. While ‘smart governance’ has drawn unprecedented interest, the combination of its conceptual vagueness and broad applications couple with a lack of focus on its underlying international and local politic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 88 publications
(136 reference statements)
1
27
0
1
Order By: Relevance
“…Moreover, external board evaluation or research on the quality of participation in the three levels of "by, of, and for" people, in practice, may be helpful to assess democratic values, such as community-building, trust, representation, efficiency, and influence. Further research is also valuable, to extend or compare the findings of this research with other smart city projects that are developed within the formal planning system [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, external board evaluation or research on the quality of participation in the three levels of "by, of, and for" people, in practice, may be helpful to assess democratic values, such as community-building, trust, representation, efficiency, and influence. Further research is also valuable, to extend or compare the findings of this research with other smart city projects that are developed within the formal planning system [65].…”
Section: Discussionmentioning
confidence: 99%
“…The neoliberal ideology and the subsequent smart city projects have caused technical, political, and economic goals to surpass social and environmental goals. Thus, it is difficult to estimate to what extent existing smart city processes or projects can keep up with a city's original expectations and ideals, such as enhanced citizen participation [65]. The dependency on competitive funding of the EU has influenced the goal-setting of the project, in which neither citizens nor their representatives engaged.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of human capital is indispensable in developing and governing smart cities. As several researchers suggest, governments must ensure that citizens attain sufficient technical and education skills to help them navigate the smart city environment [42]. Another study provided an example of the Romanian government, which created "knowledge cities" by launching e-government portals to engage stakeholders in the private and public sectors' vital services [43].…”
Section: Primary Tools In the Governance Of Smart Citiesmentioning
confidence: 99%
“…This is shown in the plans and can also be seen physically on the earth maps and by observation. We observed that according to the prerequisites of smart and sustainable cities, Brno has done very well even if it still has a lot to do to keep the balance [22,41,42,[58][59][60][61].…”
Section: Integration Between Transport Building and Green Spaces In The Citymentioning
confidence: 99%
See 1 more Smart Citation